Samson: The Strong Man - Penny Frank; Tony Morris (UK USA Lion Publishing, 1985)
Relates the story of how God sent Samson to lead the Israelites against their enemies.
color illustrations ; Australia GB8521067 bnb
"A Lion book"--Page 4 of cover.
Keywords: Theology: Miscellaneous (3GddGghJ(B: (3eJaQbGJs; Theology